Nanoscale Estimation of Coating Thickness on Substrates via Standardless BSE Detector Calibration - Skoupý, Radim; Fořt, Tomáš; Krzyžánek, Vladislav (MDPI, 2020)
The thickness of electron transparent samples can be measured in an electron microscope using several imaging techniques like electron energy loss spectroscopy (EELS) or quantitative scanning transmission electron microscopy (STEM). We extrapolate this method for using a back-scattered electron (BSE) detector in the scanning electron microscope (SEM). This brings the opportunity to measure the thickness not just of the electron transparent samples on TEM mesh grids, but, in addition, also the thickness of thin films on substrates. Nevertheless, the geometry of the microscope and the BSE detector poses a problem with precise calibration of the detector. We present a simple method which can be used for such a type of detector calibration that allows absolute (standardless) measurement of thickness, together with a proof of the method on test samples.

The thickness of electron transparent samples can be measured in an electron microscope using several imaging techniques like electron energy loss spectroscopy (EELS) or quantitative scanning transmission electron microscopy (STEM). We extrapolate this method for using a back-scattered electron (BSE) detector in the scanning electron microscope (SEM). This brings the opportunity to measure the thickness not just of the electron transparent samples on TEM mesh grids, but, in addition, also the thickness of thin films on substrates. Nevertheless, the geometry of the microscope and the BSE detector poses a problem with precise calibration of the detector. We present a simple method which can be used for such a type of detector calibration that allows absolute (standardless) measurement of thickness, together with a proof of the method on test samples.
Nanoscale Estimation of Coating Thickness on Substrates via Standardless BSE Detector Calibration
Keywords: SEM; quantitative imaging; back-scattered electrons; standardless calibration; electron mirror; sample bias; Monte Carlo simulation; thin coating layers; SEM; quantitative imaging; back-scattered electrons; standardless calibration; electron mirror; sample bias; Monte Carlo simulation; thin coating layers